2011
DOI: 10.1017/s001667231100019x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of dietary restriction and the effects of nutrient-free water and amino acid supplements on lifespan and fecundity ofDrosophila

Abstract: We measure genetic variation in lifespan and fecundity at two food levels in 34 core lines of the Drosophila Genetic Reference Panel collection. Lines were significantly different from each other in lifespan and fecundity at both restricted and full food. There was a strong food-by-line interaction for the slope of age-specific mortality, fecundity and proportion of fertilized eggs, indicating the presence of genetic variation for the strength of the dietary restriction effect, likely to represent standing gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
3
33
2
Order By: Relevance
“…These results differ from previous studies that found methionine to have a fecundityrestoring effect when fed to once-mated females (Dick et al 2011;Kabil et al 2011). Grandison et al (2009a) showed this with a concentration of methionine comparable to the one we used (0.7 mM), while the other studies got this result using a higher concentration (1.5 mM) of methionine (Dick et al 2011;Kabil et al 2011). Concentration of methionine could, therefore, potentially explain some of the discrepancy between results.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results differ from previous studies that found methionine to have a fecundityrestoring effect when fed to once-mated females (Dick et al 2011;Kabil et al 2011). Grandison et al (2009a) showed this with a concentration of methionine comparable to the one we used (0.7 mM), while the other studies got this result using a higher concentration (1.5 mM) of methionine (Dick et al 2011;Kabil et al 2011). Concentration of methionine could, therefore, potentially explain some of the discrepancy between results.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, males in mixed-sex groups on restricted diets without methionine had lower average lifespan compared to the 1.0 diet. In contrast, other studies have found a positive effect of DR on male lifespan (Magwere et al 2004;Bross et al 2005;Dick et al 2011). As it stands, we Further studies are necessary to confirm this finding, but our results highlight that nutritional effects can be sex-specific and that it is possible for lifespan-extending genetic or environmental manipulations to be only successful in one sex, with a negative or no effect on the other sex.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…While adding back all EAA (DR + EAA) shortened lifespan and restored fecundity, adding back all EAA minus methionine (DR + EAA À M) failed to shorten lifespan, indicating that methionine restriction can promote longevity. Remarkably, by manipulating each EAA individually Grandison and coauthors found that adding methionine alone to the restricted diet (DR + M) restores fecundity to normal levels but without reducing the long lifespan of DR flies (also see [21]). These findings suggest that methionine is -at least partly -responsible for the lifespan-shortening effect of full feeding, even though methionine alone (DR + M) might be insufficient to reduce longevity.…”
Section: Amino Acids Significantly Impact Lifespan and Reproductionmentioning
confidence: 99%